CONNOTATIVE MEANING IN THE PROVERBS OF THE BESEMAH LANGUAGE (A SEMATIC STUDY) - Efransyah Efransyah (IKIP Siliwangi, 2020)
The title of this research is An Analysis of Connotative Meaning in the Proverbs of the Besemah Language (A Semantic Study). Besemah language is identical of a phonem /e/ from indonesian phonem /a/. The language is used in some areas of south Sumatra especially in Lahat district, South Oku district, Bengkulu Province, and Pagar Alam City. This research was aimed to describe the connotative meaning in the proverbs of the Besemah Language. The object of this research was taken from secondary data which is the dictionary of Besemah Language written by Mahdi (2017). The writer used descriptive qualitative method in this research and some semantic theories both grand and supported theories to analyze the data. The results of this research showed that that the connotative meaning in the proverbs of Besemah Language are having great differences to denotative ones for it depends on individual experience. It means that we will understand the meaning of the proverbs from someone’s experience both through the direct story from the older people (anchestors) and witten book/dictionary. Besides, the connotative meaning of the proverbs in Besemah language mostly corelate the meaning of its proverbs to human life such responsibility, social concern, hard work, patience and love.